(untitled) (GESTIÓN Y TENDENCIAS, 2018)
The tax reform is the most significant change in this field in the last 30 years. Like any change of this magnitude, it requires a reasonable period for the actors involved to adjust. What matters is that the reform is not merely a change in the corporate income tax regime, but a new outlook on tax law grounded in the principles of justice and fairness, whereby those who have more must contribute more. Reviewing some of the less prominent changes is highly useful for a more comprehensive analysis of the reform.